Housing and socioeconomic conditions of informal settlers in Metro Manila - Cruz, Prudence Vera Paz I.
Majority of the political and economic activities take place in Metro Manila. The region generates more than 35 percent of the country_s income every year (PSA, 2015). However, it also accomodates the largest fraction of informal households with 36 percent (FIES, 2015). Several researchers associate informal settling with slum dwelling, unemployment and poverty. This makes Metro Manila an interesting case since it has consistently had the lowest poverty incidence among other regions. Using data from the 2015 Family Income and Expenditure Survey, this paper investigates the housing conditions, income and employment of informal households in Metro Manila. The results indicate good housing conditions, employment and sufficient income among majority of the households. The study finds a significant relationship between informal settling and housing conditions, and informal settling and income.